Implementation of laws and regulations on transfer of technology : the experience of the Republic of Korea - Lee, Jinjoo (United Nations New YorkUS, 1990)
Looks briefly at the laws and regulations pertaining to the transfer of technology, as well as the overall features and analysis of technology transfer.